Polychlorinated biphenyl serum levels, thyroid hormones and endocrine and metabolic diseases in people living in a highly polluted area in North Italy: A population-based study - Zani, Claudia (Heliyon, 2019)
Polychlorinated biphenyls (PCBs) are persistent organic pollutants produced until the 1980s, which they are still present worldwide. They have been associated with metabolic and endocrine diseases and hypertension in humans, but definite evidence is lacking. A chemical factory producing PCBs caused a heavy pollution in an urban area in Northern Italy. We aimed to evaluate present PCBs serum levels according to demographic and lifestyle variables and their associations with endocrine and metabolic diseases and hypertension in the resident general population. A random sample of 816 adults aged 20–79 years (mean ± SD: 49.1 ± 16.5 years) was enrolled in a cross-sectional population-based study. The participants provided a fasting blood sample for laboratory analysis and were face-to-face interviewed about the presence of chronic diseases. The serum level of total PCBs was computed as the sum of 33 PCB congeners. The median serum level of lipid-adjusted total PCBs was 435.2 and 95(th) centile was 2154.9 ng/g lipid. Medium and high chlorinated PCBs with immunotoxic and endocrine disrupting activity contributed most to total PCB serum levels, particularly PCBs 138, 153, 170, 180 and 194. The serum levels of total PCBs and of PCB functional groups were positively associated with age and negatively with female gender, education, smoking habit and BMI, and not associated with serum levels of thyroid hormones and TSH and glycaemia and with presence of endocrine diseases, diabetes and hypertension by multivariable analysis. Subgroup analyses according to gender, age and BMI provided similar results. In conclusion, this study shows a long-term persistence of past exposure to PCBs and does not support the hypothesis of an association between PCB exposure and prevalence of endocrine and metabolic diseases and hypertension.